2014
DOI: 10.1002/ar.23086
|View full text |Cite
|
Sign up to set email alerts
|

Behavior ofIn SituHuman Native Adipose TissueCD34+ Stromal/Progenitor Cells During Different Stages of Repair. Tissue‐ResidentCD34+ Stromal Cells as a Source of Myofibroblasts

Abstract: CD341 adipose stromal cells are scattered in the adipose tissue and found in the CD341 population of the stromal vascular fraction (SVF). This fraction includes adipose-derived stromal/stem/progenitor cells (ASCs), which have attracted considerable attention and show great promise for the future of regenerative medicine. Studies in this field have been undertaken mainly in vitro. In this work, however, we assessed the characteristics of human adipose tissue-resident CD341 stromal cells in normal conditions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 68 publications
(124 reference statements)
3
29
0
Order By: Relevance
“…This phenomenon may be due to a variety of cell-cell signaling promoting cell migration and interaction leading to myofibroblastic contraction pulling groupings together (Supplemental Figure 1 ). Indeed, myofibroblasts as well as other contractile cells have been found in adipose-derived SVF (Diaz-Flores et al 2015 ). Cluster size does not seem to change between inhibitor and non-inhibitor groups; however, there is an increased trend in average size of clusters over 112 h across all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon may be due to a variety of cell-cell signaling promoting cell migration and interaction leading to myofibroblastic contraction pulling groupings together (Supplemental Figure 1 ). Indeed, myofibroblasts as well as other contractile cells have been found in adipose-derived SVF (Diaz-Flores et al 2015 ). Cluster size does not seem to change between inhibitor and non-inhibitor groups; however, there is an increased trend in average size of clusters over 112 h across all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the aims of this research was to trace the presence of a specific subset of cells in deCTGs and reCTGs ubiquitously distributed throughout the body that harbour the CD34 antigen, known as" CD34+ stromal fibroblastic/fibrocytic cells (CD34+ stromal cells, CD34+ fibroblasts, CD34 + fibrocytes, telocytes)" (Díaz‐Flores et al, ; Díaz‐Flores et al, ). More recently, the same authors (Díaz‐Flores et al, ) denominated these cells as CD34+ SC/TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with the same antigenic make‐up (CD34+, CD31−, αSMA−) were traced in the stromal fraction of the tissue samples, sending prolonged cytoplasmic processes in the tissue, which is in agreement with observations from other studies (Díaz‐Flores et al, ; Roman et al, ). Because CD34+ SC/TCs have differentiation capacities and provide scaffolding support for other cells (Díaz‐Flores et al, ), they could be considered important participants in wound healing and tissue repair. However, a deeper understanding of these phenomena and of the relationship between progenitors and stem cells is of great need (Bei, Wang, Yang, & Xiao, ).…”
Section: Discussionmentioning
confidence: 99%
“…48 Indeed, Smith and colleagues 49,50 found an increase in CD34 þ cells present in TED orbital tissue. It may be that circulating CD34 þ fibrocytes are trafficked to the orbit in TED and that these cells are a major source of scar-forming myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that circulating CD34 þ fibrocytes are trafficked to the orbit in TED and that these cells are a major source of scar-forming myofibroblasts. Diaz-Flores et al 48 found that CD34…”
Section: Discussionmentioning
confidence: 99%